Chinese High School Students' Reception of American TV Series and Their Impact - Jiang Yina (SHS Web of Conferences, 2024)
In the era of increasingly developed Internet, American dramas are spreading more and more widely, and there are more and more kinds of them. This paper examines how young people reacted to American dramas when they were first introduced to China and the results that resulted from the broadcasting of the initially introduced American dramas, leading to the question of why CCTV in China did not later introduce American dramas with multiple subject genres. The researcher mainly studied the reception of information about American dramas by Chinese high school students, distributed questionnaires, and analyzed the data. According to the survey, most of the interviewees (Chinese high school students) processed the information about American dramas appropriately, and more or less produced the phenomenon of cultural adaptation, which is reflected in the fact that the contemporary Chinese high school students’ aesthetics, consumerism, and the concept of love are different from the previous traditional concepts.